TOURISM, INCLUDING AND SOCIAL RESPONSIBILITY: THE ROLE OF AMESNE MUNICIPALITIES - Sottoriva, Henrique Schiochet; Barcelos, Jéssica Talia; Steiner, Vera Lúcia (Seven Editora, 2025)
This article investigates how the municipalities of the Association of Municipalities of the Upper Northeast Slope (AMESNE) can articulate tourism and social assistance to reduce territorial inequalities and promote productive inclusion. The central research question seeks to understand how tourism can be structured as a tool for social transformation, going beyond the economic aspect to consolidate itself as an intersectoral public policy. The general objective is to analyze the role of the AMESNE municipalities in the integration between tourism, social responsibility, and assistance policies, aiming at sustainable and inclusive regional development. The specific objectives involve: (i) outlining a socioeconomic panorama of the municipalities in the region; (ii) mapping the structure of the Unified Social Assistance System (SUAS) and its interaction with tourism policies; (iii) identifying local initiatives in social and community-based tourism; and (iv) proposing strategies to strengthen productive inclusion through tourism. The methodology adopted is applied in nature, with a qualitative approach, of an exploratory and descriptive character. Documentary analysis and statistical survey techniques were used, based on secondary data from the Brazilian Institute of Geography and Statistics (IBGE), the Single Registry (CadÚnico), the Bolsa Família Program, official reports from AMESNE and SUAS, as well as national and state normative documents. Data processing involved content analysis (BARDIN, 2016) applied to plans and legislation, descriptive statistics to highlight social inequalities, and spatial analysis through georeferencing (QGIS and ArcGIS) to map vulnerable families and social protection structures. Methodological triangulation (FLICK, 2018) was employed to integrate qualitative and quantitative data, providing greater reliability to the results. The literature review consisted of an analysis of public policies on tourism and social assistance. The results show that, despite the high tourism and economic potential of the region, significant inequalities persist, highlighted by the concentration of vulnerable families. The inequalities became evident through high GDP indicators coexisting with significant social vulnerabilities, highlighted by the number of families registered in the Unified Registry and beneficiaries of the Bolsa Família Program. The structure of the Unified Social Assistance System (SUAS), composed of 49 CRAS units and 13 CREAS units, is presented as a basis for territorial social protection actions. Corroborating this evidence, it was observed that the structured presence of SUAS, associated with community-based tourism practices, professional qualification, and cultural appreciation, strengthens the social dimension of ESG, potentially reducing dependence on income transfers, generating job and income opportunities, and strengthening social cohesion. The study concludes that integrated tourism and social assistance policies have the potential to transform AMESNE into a benchmark for fair, sustainable, and inclusive regional development. DOI: https://doi.org/10.56238/sevened2025.036-091